In silico analysis and preliminary expression of antigenic fragments of OmpK and GAPDH of Vibrio species - Cahyo Budiman; Rukmiyatul Husna Rahim@Roslan; Nik Amirah Auni Nik Asri; Haslina Asis; Hollie Scarsbrook; Colin Robinson; Mohammad Tamrin Mohammad Lal; Zarina Amin (Malaysian Society for Microbiology, 2025)
Infections by pathogenic marine Vibrio bacteria lead to high fatalities in grouper and cause systemic diseases in various fish, crustaceans, and molluscs, resulting in significant economic losses in the aquaculture industry. The use of antibiotics has led to antimicrobial resistance in aquaculture systems, prompting the exploration of vaccines as an alternative solution. Currently, full-length outer membrane protein K (OmpK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) from various Vibrio species are being explored as vaccine candidates. However, little is known about the potential of using antigenic fragments. Moreover, no data exists on combining OmpK and GAPDH proteins as a bivalent vaccine candidate against vibriosis. This study investigates the potential of antigenic fragments from combined OmpK and GAPDH as a bivalent vaccine candidate against vibriosis. The amino acid sequences of OmpK and GAPDH proteins from three species known to infect fish-V. parahaemolyticus, V. harveyi, and V. alginolyticus-were retrieved from the GenBank database. Their physicochemical properties were analyzed using PROTEIN CALCULATOR, and antigenic fragment prediction was conducted using BepiPred, Emini Surface Accessibility, and Kolaskar & Tongaonkar Antigenicity methods from the IEDB Analysis Resource. The selected fragments were expressed using a pET30a vector in Escherichia coli BL21(DE3), linked by a flexible linker and tagged with a His-tag for purification. Overexpression was induced with IPTG, and the proteins were harvested and analyzed by SDS-PAGE. The sequences of OmpK and GAPDH showed high similarity, with more than 85% and 70% identity, respectively. Physicochemical properties varied between the proteins but were comparable within the same protein type across different species. Antigenic fragment prediction identified the fragments of Ile76-Phe151 and Ala140-Thr235 as the best epitope candidates for OmpK and GAPDH, respectively. Expression of the genes encoding these fragments demonstrated that the combined OmpK and GAPDH antigenic fragments were successfully expressed in a bivalent form in E. coli BL21(DE3), with approximately 50% of the expressed proteins being in soluble form. This study successfully demonstrated the expression of combined OmpK and GAPDH antigenic fragments from Vibrio species as potential bivalent vaccine candidates against vibriosis. Although the solubility of the fused OmpK-GAPDH protein needs improvement, this research opens new opportunities to explore the immune-protective potential of these fusion fragments against vibriosis in marine organisms.